Penggunaan Bahasa Inggris pada Usaha Kuliner: Tujuan Produsen dan Perspektif Konsumen - Nawa, Agus Trioni (Tapis: Jurnal Penelitian Ilmiah, 2023)
Foreign languages ​​are now widely used in Indonesia, one of which is the use of English in culinary businesses. This is done by culinary entrepreneurs of course for reasons and to promote specific perspectives for consumers. This research aimed to reveal the meaning behind the use of English in culinary businesses and what perspectives emerged from this phenomenon. This research used a qualitative descriptive approach involving free structured interviews with culinary entrepreneurs in Metro City and consumers. Analysis was carried out by compiling concepts, categorizing data, and exploring relationships between categories, discourse and drawing conclusions. The research showd that the first aim of using English in culinary business were a marketing strategy to attract consumer interest by presenting different concepts so that it could generate curiosity for potential consumers; secondly as an adaptation to the times. Furthermore, the community's perspective on the use of English in culinary businesses were to foster curiosity to try; make an impression, modern, cool, international standard, professional, expensive, upper social class, trendy, luxurious; for young only; and time inefficient.